Highly selective claisen-schmidt condensation catalyzed by silica chloride under solvent-free reaction conditions - Hazarkhani, Hassan; Kumar, Pradeep; Kondiram, Kadam Sachin; Gadwal, Ikhlas M. Shafi (Synthetic Communications, 2010)
Silica chloride serves as a useful catalyst in the cross-aldol condensation, leading to the synthesis of a wide variety of bisarylidene cycloalkanones and chalcones. The catalyst showed high selectivity; self-condensation of ketones was not observed.
Keywords: Aldol reaction; arylidene cycloalkanone; Claisen-Schmidt; condensation; silica chloride